2009
DOI: 10.1021/es901296t
|View full text |Cite
|
Sign up to set email alerts
|

Brominated Flame Retardants in Serum from the General Population in Northern China

Abstract: In 2006, 128 serum samples were collected from three populations in Tianjin, China: office cleaners, university students, and policemen. These samples were all analyzed for polybrominated diphenyl ethers (PBDEs) and for other brominated flame retardants (BFRs). The median concentration of total PBDEs (sum of 41 congeners) was 7.1 ng/g lipid, ranging from 0.48 to 1980 ng/g lipid. Among these PBDE congeners, the median sum of the tri- to hepta-PBDE (SigmaPBDE3-7) congener concentrations was 2.9 ng/g lipid, rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
38
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(49 citation statements)
references
References 42 publications
9
38
2
Order By: Relevance
“…4. The PBDE pattern in the hair from the nonoccupationally exposed residents in different areas (rural, urban, and the e-waste) in this study were similar to those in human serum samples from general population in China (Zhu et al, 2009), suggesting that endogenous exposure might be a major source for the human hair PBDEs. Moreover, as shown in the Fig.…”
Section: Roles Of Dust As Source Of Hair Bfrssupporting
confidence: 65%
See 1 more Smart Citation
“…4. The PBDE pattern in the hair from the nonoccupationally exposed residents in different areas (rural, urban, and the e-waste) in this study were similar to those in human serum samples from general population in China (Zhu et al, 2009), suggesting that endogenous exposure might be a major source for the human hair PBDEs. Moreover, as shown in the Fig.…”
Section: Roles Of Dust As Source Of Hair Bfrssupporting
confidence: 65%
“…It is worth to compare the PBDE profiles in the hair with the serum samples reported by other previous studies (Antignac et al, 2009;Bi et al, 2007;Harrad and Porter, 2007;Kalantzi et al, 2010;Sjödin et al, 2008;Zhu et al, 2009). Due to the sets of congeners reported in different studies are not identical each other, we could only summed the most commonly reported congeners (BDE 47,99,100,153,154 and 183) and normalized them to 100%.…”
Section: Roles Of Dust As Source Of Hair Bfrsmentioning
confidence: 99%
“…This is reasonable because in China, deca-BDEs are produced and used in large quantities, penta-BDEs were once extensively produced but banned in 2006, and octa-BDEs have never been produced or used in China (Chen et al 2012). Zhu et al (2009) used a similar method to estimate the contribution of the three PBDE products and then speculated the possible transformation of PBDE congeners according to the deviations between their predicted and measured data. In our study, the average predicted percentages for BDE-209 in the studied areas (80.12, 77.88, 88.28, and 92.51 %) only show deviations <0.15 % away from the corresponding measured data (80.26, 77.93, 88.29, and 92.63 %).…”
Section: Pbdesmentioning
confidence: 99%
“…Based on the knowledge of their adverse effects on the environment and human health, some PBDEs have been included on the Stockholm Convention list of priority persistent organic pollutants, and some technical products have been banned or voluntarily withdrawn from use in some regions of the world (California State Assembly, 2003;Cox and Efthymiou, 2003). However, owing to their high volume production, long-term use, and lipophilic and persistent properties, PBDEs are still frequently detected in various environmental media (Kim et al, 2014;Newton et al, 2015) and biotic samples (Shang et al, 2013;Wang et al, 2014;Zhu et al, 2009) in the environment. Therefore, there is considerable concern about their behaviors and fates in the environment.…”
Section: Introductionmentioning
confidence: 99%